Index modulation aided frequency hopping anti-jamming and encryption method based on rotation scrambling - Xinjin LU; Jing LEI; Yuxin SHI (Tongxin xuebao)
In order to improve the anti-jamming ability and security of the wireless communication system， an index frequency-hopping anti-interference encryption method based on rotation scrambling was designed， which could be simply called encrypted index modulation frequency hopping spread spectrum （EIM-FHSS）.Firstly， the wireless secret key was used to control multiple orthogonal frequency hopping patterns to determine the available frequencies at the current moment.The index of the active frequency （the frequency point with the modulation symbol） was used to transmit the bit information.Secondly， the secret key was used to employ scrambling encryption on the mapping table between information bits and the indexes， to ensure the security of the index bits.Finally， constellation rotation encryption was used on the symbols transmitted on the active frequency in the scheme， which ensured the security of symbol bits.Theoretical analysis and simulation results show that the proposed EIM-FHSS method has stronger security and anti-jamming abilities than the traditional IM-FHSS methods.